The Effect of F516 (Pyraclostrobin + Anilide) on Brown Rot (Monilinia spp.) Control at Peach Orchards of San Pedro, Argentina - Constantino, Armando (2006)
Brown rot is a major disease affecting peach orchards of Buenos Aires province, Argentina. Carbendazim resistant Monilinia strains were found in several peach orchards of San Pedro, so the use of this fungicide is restricted to one application during the growing season. The authorized systemic fungicides registered for peach orchards in Argentina, belong all to the demethylation inhibiting (DMI) family. These fungicides are effective against brown rot, but could induce resistance problems if used regularly. The fungicide F516 contains strobilurin (pyraclostrobin) and anilide (nicobifen) as active ingredients. The objective of this work was to determine if F516 sprays at early season (ES) and preharvest (PREH) controls fruit brown rot caused by Monilinia spp. and to compare the effectiveness with the most control practices followed by peach growers. Trials were conducted at INTA San Pedro, on cvs. ‘Flordaking’, ‘Kurakata’ and ‘Red Globe’. Trials were performed in 2002/03 and 2003/04, testing the following treatments: 1. Unsprayed check, 2. Sulfur (ES)/Tebuconazole (PREH), 3. Sulfur (ES)/F516 (PREH), 4. F516 (ES)/tebuconazole (PREH), 5. F516 (ES)/F516 (PREH); Sulfur 600 g/100 L (WP 80%), Tebuconazole 30 mL/100 L (EC 43%) and F516 50 mL/100 L (EC 10% + 20%). The fungicide F516 provided very good brown rot control, either at ES and PREH sprays. The addition of F516 to the list of fungicides registered for use in peach orchards could allow improvement of the pesticide resistance management strategy.